Morphogenesis and formation of the human hyoid bone - Tsyhykalo, O. V.; Popova, I. S.; Khodorovska, A. A. (Морфологія / Morphologia / Morfologìâ, 2020)
Background. Morphogenesis of hyoid bone in early intrauterine development of human is a topical question of anatomical research that is aimed to improve methods of surgical interventions in neck and mandible regions and to supplement data in forensic practice. Objective. To investigate peculiarities of development and morphological transformations of hyoid bone in the early period of human ontogenesis. Methods. 15 specimens of human embryos and prefetuses of 12,0-80,0 mm parietal-coccygeal length (PCL) were investigated by using a set of morphological methods. Results. In human embryos 12,0-13,5 mm PCL, rudiment of hyoid bone is seen as s mesenchymal condensation in second pharyngeal arch area above the level of cervical sinus. In 13,0-13,5 mm PCL embryos, hyoid bone anlage is on prechondrification stage: caudal segment of Reichert’s cartilage forms small horns and mesodermal condensation of III pharyngeal arch forms large horns and body of hyoid. In 50,0-80,0 mm PCL human prefetuses, hyoid part of Reichert’s cartilage, which forms small horns, reaches chondrification stage. The body and large horns of hyoid are connected to small horns, and are found lower the level of tongue anlage. At this stage hyoid bone is an attachment site for the hyoid neck muscles. Conclusions. 1. Rudiment of the hyoid bone is found at the end of embryonic period as a prechondrificational mesenchymal condensation of II and III pharyngeal arches 2. During prefetal period, small horns loose contact with the cranial part of Reichert’s cartilage. 3. Anlage of the hyoid bone during prefetal period is on chondrification stage and is a site of attachment for supra- and infrahyoid muscles.